Penegakan Hukum Pidana terhadap Orang yang Turut Serta (Deelneming) Melakukan Tindak Pidana Merampas Kemerdekaan Orang Lain (Studi Kasus : Putusan Nomor 220/Pid.B/2019/PN.Bdg) - Ramdhani, Romi; Apriani, Rani (Jurnal Ilmiah Wahana Pendidikan, 2024)
In recent times, the form of crime is increasingly showing its complexity, which is highly complicated when viewed from various aspects. One of the crimes that is quite prevalent today is a crime against the freedom of others. This clearly violates the provisions of Human Rights (HAM) as well as the 1945 Constitution. The Indonesian Criminal Code (KUHP) itself has to some extent regulated the provisions regarding crimes against the freedom of others, which are stipulated in Book III Chapter XVIII. A recent case that has caught public attention is the Defendant Muhamad Abdul Basit Iskandar, who has been proven to have engaged in actions that aided or facilitated others in committing the crime of deprivation of liberty. Muhamad Abdul Basit Iskandar was found to have assisted Defendant Habib Bahar bin Smith, who, in essence, was involved in the criminal acts of assault and crimes against the deprivation of the freedom of others. As a result, Muhamad Abdul Basit was sentenced to 1 (one) year and 6 (six) months in prison. This study uses a normative juridical approach, involving an examination of legal principles, legal systematics, the level of legal synchronization, and legal comparisons. It also discusses legal doctrines or principles in legal science. The legal regulation regarding someone who participates (deelneming) in committing the crime of depriving others of their freedom, based on the Indonesian Criminal Code (KUHP), is stipulated in Article 333 in conjunction with Article 55 of the KUHP. One of the factors influencing the Defendant is the presence of external factors or factors outside the perpetrator's control. Additionally, there are internal factors within the perpetrator and environmental factors when carrying out criminal acts that were previously discussed among individuals when there are circumstances causing harm in that environment. The criminal law enforcement against someone who participates (deelneming) in committing the crime of depriving others of their freedom is related to the actions or deeds carried out by the defendant and cannot be separated from criminal responsibility, resulting in harm to the witnesses Cahaya Abdul Jabar and witness Muhammad Khoerul Umam Almudzqi.